2020
DOI: 10.1021/acsomega.0c01519
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,4-Biphenyl-triazole Derivatives as Possible 17β-HSD1 Inhibitors: An in Silico Study

Abstract: Triazoles occupy an important position in medicinal chemistry because of their various biological activities. The structural features of 1,2,3triazoles enable them to act as a bioisostere of different functional groups such as amide, ester, carboxylic acid, and heterocycle, being capable of forming hydrogen bonds and π−π interactions or coordinate metal ions with biological targets. In this work, the synthesis of 1,2,3-triazole derivatives via copper(I)-catalyzed azide−alkyne cycloaddition (CuAAC) is reported.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Stretching vibrations at 1754, 1725, 1710, and 1690 cm −1 are assigned to ester carbonyl, free urethane carbonyl, disordered hydrogen‐bonded urethane carbonyl, and ordered hydrogen‐bonded urethane carbonyl, respectively 46 . The value of hydrogen bonding (X B,U ) is calculated and listed in Table S4 47,48 . As shown in Table S4, the X B,U value increases greatly after the degradation, and the percentage of ester groups decreases significantly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stretching vibrations at 1754, 1725, 1710, and 1690 cm −1 are assigned to ester carbonyl, free urethane carbonyl, disordered hydrogen‐bonded urethane carbonyl, and ordered hydrogen‐bonded urethane carbonyl, respectively 46 . The value of hydrogen bonding (X B,U ) is calculated and listed in Table S4 47,48 . As shown in Table S4, the X B,U value increases greatly after the degradation, and the percentage of ester groups decreases significantly.…”
Section: Resultsmentioning
confidence: 99%
“…46 The value of hydrogen bonding (X B,U ) is calculated and listed in Table S4. 47,48 As shown in Table S4, the X B,U value increases greatly after the degradation, and the percentage of ester groups decreases significantly. After 60 days of enzymatic degradation, the percentage of ester groups decreases from 40.9% to 10.5%, while the value of X B,U increases from 33.7% to 75.7%, indicating that after the enzymatic degradation, most of the ester groups are hydrolyzed, and the retaining hard segments have a high degree of hydrogen bonding due to the increasing density of urethane groups.…”
Section: Degradation Behaviors Of Pptr-pu Filmmentioning
confidence: 93%
“…Standard deviation (s), Fishers F-test (F), and the coefficient of determination (R 2 ) were used for the model validation. For the predictive ability evaluation of the model, we used the cross-validation coefficient (Q 2 LOO ) with the Leave-One-Out (LOO) method; due to the small number of compounds used for this model, Q 2 LOO gives us a quality evaluation of its prediction ability [40].…”
Section: Mathematical Model For Ic 50 Predictionmentioning
confidence: 99%
“…Previous studies have shown that they are excellent candidates for the treatment of various types of plant and animal diseases [ 16 , 17 , 18 ]. Thus, a range of triazole compounds has been reported as medicinal drugs and good molecular scaffold candidates, Human 17β-hydroxysteroid dehydrogenase type 1(17β-HSD1) inhibitors, antifungal, anticancer, antibacterial, antitubercular, antiviral, anti-inflammatory, analgesic, anticonvulsant, antiparasitic, and other health and related pharmacological and biological conditions [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The structural features of 1,2,3-triazoles enable them to act as a bioisostere of different functional groups such as carboxylic acid (–COOH) and its amide (–CONH 2 ) and ester (–COOR) derivatives. Again, the triazole group is capable to form hydrogen bonds which makes its derivatives more polar and soluble in most systems and their ability to form π−π interactions and also easily coordinate to metal ions serves as a good substrate for biological targets, thus making them good template for the synthesis of medicinal compounds [ 19 ]. Here, we report the synthesis of ten 1,2,3-triazole compounds containing thymol moiety, and their antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%